Kontribusi Human dan Sistem Gudang terhadap Ketidak Sesuaian Stok Inventory - Ferdian kosagiama; Muhamad Fian; Damar Eulan; Muhamad Ilham; Yudi Prastyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Inventory record inaccuracy remains a critical challenge in warehouse operations due to the complex interaction between human factors and warehouse systems. This study aims to analyze the contribution of human and warehouse system factors to inventory stock discrepancies at PT. LOGISTIC’s warehouse using a descriptive–analytical case study approach. The research adopts the DMAIC framework combined with root cause analysis to identify operational weaknesses affecting inventory accuracy. The results indicate that human-related issues, including data input errors, non-compliance with standard operating procedures, and limited verification practices, constitute the dominant sources of inventory discrepancies. In parallel, warehouse system limitations such as delayed WMS synchronization, scanner reliability issues, and insufficient system validation mechanisms significantly contribute to data inaccuracies. The improvement in inventory accuracy from 97.45 percent in the first count to 98.55 percent in the second count demonstrates that manual verification remains essential, highlighting the reactive nature of existing control mechanisms. These findings suggest that effective inventory control requires an integrated approach that aligns human competence, standardized operational processes, and system optimization to achieve sustainable inventory accuracy.